Experimental study of freeze vacuum drying with thermal energy storage for drying 2 kg aloe vera - Warits Adriyandy; Wulan Cahyati; Dinni Agustina; Awaludin Martin (BKS-TM Indonesia, 2025)
One of the widely used post-harvest processing methods for aloe vera is drying, given its high water content. An effective drying method is vacuum freeze-drying, although this method has a drawback in energy efficiency. This research examines the use of paraffin wax as a Thermal Energy Storage (TES) medium to utilize waste heat from the condenser during the freezing phase in a vacuum freeze-drying system. The results of the study show that the use of TES consistently improves drying efficiency and energy savings. The system with TES was able to remove a higher moisture content compared to the test without TES, at 68% for a 2 kg load versus 58.57% without TES. In addition, the Coefficient of Performance (COP) for the system with TES was recorded at 2.23, which is higher than the 2.08 without TES. The use of TES for 2 kg also resulted in an electrical energy saving of 259 Wh. Thus, TES in a vacuum freeze-drying system is effective in enhancing energy efficiency, reducing power consumption, and improving the drying performance of aloe vera.